Seasonal Variation of Physico-Chemical Parameter of a Non Saline water Area, Indra Gandhi Nahar in Surewala Village, District Hanumangarh, Rajasthan: Assessment of Seasonal Variation in Physico-Chemical Parameters of Indra Gandhi Nahar in Surewala Village (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Recent research deals with the analysis of fresh water quality of Indra Gandhi Nahar in Surewala Hanumangarh District with regards to physical-chemical factors like water Thermogenesity of water , Hydrogen ion concentration, Electrical conductivity(EC), Turbidity, Dissolved oxygen (DO), Total alkalinity (TA), Total Hardness, Total Dissolved Solid, Chloride and phosphate (PO43-). The physico chemical characteristic of Indra Gandhi Nahar in Surewala villege is found to be highly fluctuated with seasonal variations during the present investigation. Higher level of DO analysed during winter season and that represent reciprocity against Thermogenesity of water, TDS, EC which have higher level in summer. The researches explain that the quality of water is higher than fresh water limits and highly polluted.